Estimate and Evaluation of Drug Nephrotoxicity Caused with Most Used Medicals in Patients with Rheumathoid Arthritis - Dejan Spasovski (Archives of Clinical Nephrology - Peertechz Publications, 2016)
Aim: To estimate the effect of initial therapy with Paracetamol (Acetaminophenum) and nonsteroidal anti-inflamatory drugs (Ketoprofenum) on glomerular and tubular integrity in patients with Rheumatoid arthritis (RA), to quantify toxicity of these drugs through measurements of the enzyme excretion that correlates with the damage degree on the tubular epithelium. Microalbuminuria is used as marker for glomerular damage, and the urinary excretion of N-Acetyl-β-D-glucozaminidase (NAG) as an indicator of proximal tubular damage. To determine if there is a change in the clinical indicators of renal function (serum urea and creatinine, urine urea and creatinine, glomerular filtration rate - GFR) in the course of disease and if that change correlates with the dynamics of the quantity of excreted enzymes in urine, reactants of the acute pfase and index of disease activity (DAS28).   Methods: Using the colorimetric method for determination of NAG, as well as immunoturbidimetric immunoturbidimetric assay for detection of microalbuminuria, we examined samples of 70 participants (35 RA pts treated only with Paracetamol, 35 RA pts treated with Ketoprofen), followed up in five time intervals in the course of 24 weeks. Rheumatoid factor (RF) is determined with the agglutination test (Lateks RF test) in the same participants. Results: there is a weak correlation between NAG and microalbuminuria (r=0.16) in the group of patients treated with Paracetamol, while in the group treated with Ketoprofen there is moderate correlation (r=0.28). NAG enzymuria in range, in number of examined patients and in time of appearance is greater and appears earlier in the group with Ketoprofen compared with the group of Paracetamol. Conclusions: Ketoprofen is more potent NAG inductor and triggers greater tubular enzymuria than Parcetamol.